Descrição e filogenia de um novo espécime de cinodonte probainognátio do triássico sul-brasileiro - Stefanello, Micheli (2018)
The present dissertation aims to describe the cranial anatomy of a new specimen of Ecteniniidae, CAPPA/UFSM 0029, collected in Upper Triassic rocks. The new specimen, which comes from the Janner outcrop in the outskirts of the municipality of Agudo, Rio Grande do Sul, Brazil, is included in Santa Maria Supersequence, Candelária Sequence (Hyperodapedon Association Zone – Carnian). Among the several clades of probainognathian cynodonts recorded from Middle and Upper Triassic strata in South America, Ecteniniidae is one of the most enigmatic groups, characterized by the combination of basal and derived characters, whose record is still scarce. Until now, the clade comprise three species, Ecteninion lunensis and Diegocanis elegans from Argentina, and a single Brazilian taxon, Trucidocynodon riograndensis. In this study, we report an almost complete skull and lower jaw of a new and large specimen of Trucidocynodon riograndensis, which increases the representativeness of this probainognathian clade for the Late Triassic of Southern Brazil. The phylogenetic analysis recovered CAPPA/UFSM 0029 in a sister-group relationship with Trucidocynodon riograndensis, both in a trichotomy with Ecteninion lunensis and Diegocanis elegans, forming the clade Ecteniniidae. CAPPA/UFSM 0029 shares with the holotype UFRGS PV-1051-T a unique combination of features, which allowed its attribution to Trucidocynodon riograndensis: (i) extranasal process of the premaxilla large but not contacting the nasal; (ii) pterygoparoccipital foramen anteriorly open; (iii) posterior opening of the post-temporal foramen limited by the tabular and the squamosal; and (iv) external dorsal opening of the paracanine fossa. CAPPA/UFSM 0029 is the largest known ecteniniid specimen so far collected, so it contributes to the knowledge of the variation of the body size within the clade. Moreover, the new specimen, together with other ecteniniids, provides additional evidence that carnivore probainognathian cynodonts played a significant role in the Late Triassic ecosystems and represented an endemic radiation in Southwestern Gondwana.